Monitoring colonoscopy withdrawal time significantly improves the adenoma detection rate and the performance of endoscopists - Vavricka, Stephan R.; Sulz, Michael C.; Degen, Lukas; Rechner, Roman; Manz, Michael; Biedermann, Luc; Beglinger, Christoph; Peter, Shajan; Safroneeva, Ekaterina; Rogler, Gerhard; Schoepfer, Alain M. (Endoscopy, 2016)
Background and study aims: The recommended minimum withdrawal time for screening colonoscopy is 6 minutes. Adenoma detection rates (ADRs) increase with longer withdrawal times. We aimed to compare withdrawal times and ADRs of endoscopists unaware of being monitored vs. aware.Patients and methods: Seven experienced gastroenterologists prospectively performed 558 screening colonoscopies during a 9-month period in a Swiss University hospital. Colonoscopy withdrawal times were first measured without the gastroenterologists’ knowledge of being monitored (n = 355 colonoscopies) and then with their knowledge (n = 203 colonoscopies).Results: The median withdrawal time when gastroenterologists were unaware of being monitored was 4.5 minutes (interquartile range [IQR] 4 – 5.5 minutes) without intervention and 6 minutes (IQR 4 – 9 minutes) with intervention, increasing significantly to 7.3 minutes (IQR 6.5 – 9 minutes) and 8 minutes (IQR 7 – 11 minutes), respectively, when they were aware of being monitored (P < 0.001 both for colonoscopies with and without intervention). The ADR increased from 21.4 % when the gastroenterologists were unaware of being monitored to 36.0 % when they were aware (P < 0.001). In the multivariate regression model, the endoscopists knowing they were being monitored was the strongest factor associated with ADR (odds ratio 4.417; 95 % confidence interval [CI] 2.241 – 8.705; P < 0.001).Conclusions: Colonoscopy withdrawal time in unmonitored gastroenterologists is shorter than recommended and increases with awareness of monitoring. ADR significantly increases when gastroenterologists are aware of being monitored. Implementation of systematic monitoring, and analysis of withdrawal time and ADR for each endoscopist may help to increase the ADR.